Accidentability at Arequipa: a bibliometrical study from written press since 2000 to 2009 - Arias Gallegos, Walter (2016)
The objective of this study was to analyze some occurrence features of working accidents in three sectors of production (Industry, Mining and construction) at Arequipa City since 2000 to 2009. We work with bibliometrical method in a descriptive research design, in which analysis units were 3653 newspapers of the city, where there were extracted the data related to working accidents in the city by using a register file specially designed. We found that the most vulnerable sector was industry, and it is followed by construction and mining, because of the occurrence of accidents, perhaps the mortal victims are more in sector of construction. In three sectors there is a tendency to downsize accidents, which is marked in construction. Moreover, the types of accidents registered most frequent were drops, cuts, explosions and intoxications. We conclude that accidents in Arequipa are downsizing slowly and the records of accidents are lower than other cities in Latin America.